Risk Priority Determination Using FMEA and AHP Integration: Penentuan Prioritas Risiko Melalui Integrasi FMEA dan AHP - Mochamad Iqbal Latif; Hana Catur Wahyuni (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Risk management plays a crucial role in maintaining productivity and operational stability in industrial systems. Specific Background: Many production processes experience failures that lead to decreased performance due to unstructured identification and prioritization of risks. Knowledge Gap: Previous studies often apply Failure Mode and Effect Analysis (FMEA) and Analytical Hierarchy Process (AHP) separately, limiting the ability to systematically determine risk priorities. Aims: This study aims to identify potential failures, assess risk levels, and determine priority mitigation strategies using an integrated FMEA and AHP approach. Results: The analysis identified multiple failure modes with varying Risk Priority Number values, where dominant risks were determined through severity, occurrence, and detection criteria. The AHP method produced weighted priorities that guided the selection of key mitigation actions. Novelty: This study presents an integrated framework combining FMEA and AHP to support structured and hierarchical risk prioritization. Implications: The findings provide a practical basis for decision making in managing operational risks and improving process reliability through prioritized mitigation actions. Keywords: Risk Management, FMEA, Analytical Hierarchy Process, Risk Priority, Mitigation Strategy Key Findings Highlights Failure modes are systematically ranked based on multi-criteria evaluation Decision weights guide selection of critical corrective actions Integrated framework supports structured operational risk handling